If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 6 = -60 + 4x Reorder the terms: 6 + -2x = -60 + 4x Solving 6 + -2x = -60 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 6 + -2x + -4x = -60 + 4x + -4x Combine like terms: -2x + -4x = -6x 6 + -6x = -60 + 4x + -4x Combine like terms: 4x + -4x = 0 6 + -6x = -60 + 0 6 + -6x = -60 Add '-6' to each side of the equation. 6 + -6 + -6x = -60 + -6 Combine like terms: 6 + -6 = 0 0 + -6x = -60 + -6 -6x = -60 + -6 Combine like terms: -60 + -6 = -66 -6x = -66 Divide each side by '-6'. x = 11 Simplifying x = 11
| -12+8=-2 | | 9+4x-17=12 | | 3x+185=180 | | 3x/7=-4/9 | | -10+x=-6x-80 | | 4m+3m+8=12 | | 5x43/10 | | 14=x-3x-4 | | 2x+90+x+95=180 | | 5t-1=t/3-17 | | -4+(-2+1)+5-(3-(1-2)+4)+1-2= | | 12X=4X-60 | | 4z/7-5=10 | | -7x+10-3x=-10 | | -w^2+6w-9=0 | | 196x^2y+80x^3+120y^2x= | | 70+80=180 | | X^2+14x=176 | | 51=7x+3x+1 | | (-7*28)+(-7*75)=-7(28+r) | | 3k^2-10k-18=-6k^2+3 | | 110=5y^2+20 | | v^2+6=86 | | -1=-7x+5x-5 | | 7k^2=-9k-9 | | z/7-8=4 | | 3(7-2w)=3(w+5)-84 | | 9x^2-51x+30=0 | | -x-y-2=0 | | 8a^2-1=127 | | 11+65=72 | | 4X=6X+48 |